2014
DOI: 10.5367/ihe.2014.0223
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Financial Management Practices by Small, Medium and Micro Enterprises: A Perspective from South Africa

Abstract: This paper reports on an investigation of financial management practices used by small, medium-sized and micro-enterprises (SMMEs) in South Africa. It was found that more than half the SMMEs examined use external accounting staff to prepare accounting reports and more than 60% rely on external accounting staff to interpret and use accounting information. A majority of the SMME owners were found to lack interpretation skills and an awareness of how to use information from financial statements. An impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…Furthermore, Brijlal, Enow and Isaacs (2014) observed that financial management education and training of SMEs is vital for success of their businesses and called upon financial institutions to take a leading role in spearheading training and skills development. When business owners have no personal training in financial management, they typically make use of external financial management consultants, which unfortunately, small business retailers cannot afford, as cited by Brijlal et al (2014).…”
Section: 28mentioning
confidence: 99%
“…Furthermore, Brijlal, Enow and Isaacs (2014) observed that financial management education and training of SMEs is vital for success of their businesses and called upon financial institutions to take a leading role in spearheading training and skills development. When business owners have no personal training in financial management, they typically make use of external financial management consultants, which unfortunately, small business retailers cannot afford, as cited by Brijlal et al (2014).…”
Section: 28mentioning
confidence: 99%
“…Of the participants that do offer credit facilities, 7.6% (n=250) do not calculate the percentage of credit as a portion of their total sale, 3.2% (n=250) indicated that between 25% and 49% of their monthly sales is on credit and 19.2% n=250indicated that between 50% and 74% of their monthly sales is on credit. Brijlal et al (2014) opine that cash management is very important to the financial well-being of a SMME. Whilst the provision of credit facilities can serve to attract customers, it should be stated that if credit sales are allowed and the business owner does not accurately record these sales, he/she will have difficulty in recouping their accounts that are receivable.…”
Section: Percentage Of Monthly Sales On Creditmentioning
confidence: 99%
“…However, the same respondents also indicated that they did not perceive an internal audit as adding value to the company's financial performance. However, Brijlal et al (2014) advocate that internal audits can be conducted in a cost effective manner by the SMME owner and should result in enhanced financial control. Section C: Operational Characteristics Indicate the generic strategy that your business has adopted The figure above illustrates that the most common generic strategy that has been adopted by SMME owners is a cost leadership strategy (46.4%).…”
Section: Arabian Journal Of Business and Management Review (Nigerian mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, survey of the existing literature (e.g. Brijlal et al, 2014;Tayles, Pike & Sofian, 2007; indicates shortage of empirical studies that integrate costing, budgeting, and performance measurement practices with moderating variable of the external business environment, although few studies have indicated how costing, budgeting, performance measurement practices, and external business environment can stimulate profit growth and drive forward performance. Also, there is dearth of research regarding the use of external business environment as moderator in the context of SMEs (Drury & Tayles,1995;Alkizza& Akbar, 2006;CGA, 2010;Shehu& Mahmood, 2014).In Sudan, the application of management accounting practices (MAPs) in SMEs is limited, and there are few studies relating MAPs usage to the performance of SMEs.…”
Section: Introductionmentioning
confidence: 99%